2018
DOI: 10.1136/tobaccocontrol-2018-054390
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, experience and prevalence of heated tobacco product, IQOS, among young Korean adults

Abstract: IntroductionPhilip Morris International introduced ‘IQOS’ to the Korean market in June 2017. To monitor the use of IQOS among young Korean adults, we identified their awareness, experience and current use of IQOS.MethodsThree months after the introduction of IQOS in Korea, we conducted an online survey with 228 general young adults, aged 19–24 years.Results87 participants (38.1%) were aware of IQOS, 13 (5.7%) were IQOS ever users and 8 (3.5%) were current IQOS users. All the current IQOS users were triple user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
104
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 4 publications
10
104
3
1
Order By: Relevance
“…Furthermore, the analysis of the same PMI MTRP application by Glantz [84] suggested that, in human testing, IQOS did not reveal detectably better measures of the biomarkers of potential Gale HTPs 180 Japanese adult smokers (aged 33± 9.0 years; 50% male); THP1.0 (glo), THS2.2 (IQOS), a combustible cigarette; the smokers smoked combustible cigarettes for 2 days; after this period, they were switched to the following groups: 1) continue smoking, 2) switch to the mentholated or non-mentholated variant of glo, 3) switch to non-mentholated IQOS, or 4) quit nicotine and tobacco product use; each group used their dedicated products for 5 days; the baseline and post-randomization 24-h urine samples were collected, carbon monoxide in exhaled breath was measured daily -glo or IQOS use for 5 days reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use on day 5 after switching, the urinary biomarkers of toxicants (except the nicotine) and exhaled CO levels were significantly reduced by medians 21-92%, compared with the baseline in all groups using glo or IQOS, or quitting tobacco use BAT -British American Tobacco; CO -carbon monoxide; ppm -parts per million; HPHCs -harmful and potentially harmful constituents; HTPs -heated tobacco products; PMI -Philip Morris International; THP1.0 -tobacco heating product (glo); THS2.1 -tobacco heating system 2.1 (the prototype of IQOS); THS2.2 -tobacco heating system 2.2 (IQOS); 3R4F -reference cigarette. IQOS users were triple users of conventional cigarettes and e-cigarettes, as well as HTPs [86]. HTPs have also gained popularity in the USA [87,88].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the analysis of the same PMI MTRP application by Glantz [84] suggested that, in human testing, IQOS did not reveal detectably better measures of the biomarkers of potential Gale HTPs 180 Japanese adult smokers (aged 33± 9.0 years; 50% male); THP1.0 (glo), THS2.2 (IQOS), a combustible cigarette; the smokers smoked combustible cigarettes for 2 days; after this period, they were switched to the following groups: 1) continue smoking, 2) switch to the mentholated or non-mentholated variant of glo, 3) switch to non-mentholated IQOS, or 4) quit nicotine and tobacco product use; each group used their dedicated products for 5 days; the baseline and post-randomization 24-h urine samples were collected, carbon monoxide in exhaled breath was measured daily -glo or IQOS use for 5 days reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use on day 5 after switching, the urinary biomarkers of toxicants (except the nicotine) and exhaled CO levels were significantly reduced by medians 21-92%, compared with the baseline in all groups using glo or IQOS, or quitting tobacco use BAT -British American Tobacco; CO -carbon monoxide; ppm -parts per million; HPHCs -harmful and potentially harmful constituents; HTPs -heated tobacco products; PMI -Philip Morris International; THP1.0 -tobacco heating product (glo); THS2.1 -tobacco heating system 2.1 (the prototype of IQOS); THS2.2 -tobacco heating system 2.2 (IQOS); 3R4F -reference cigarette. IQOS users were triple users of conventional cigarettes and e-cigarettes, as well as HTPs [86]. HTPs have also gained popularity in the USA [87,88].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
“…Ever e-cigarette users were also more likely to be aware of HTPs [85]. In Korea and the USA, the highest awareness and ever or current use of HTPs were also observed among current smokers or e-cigarette users [86,87].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…IQOS is currently sold in more than 40 countries or regions world‐wide, particularly in high‐income countries . After becoming popular and widely used in Japan , IQOS has also gained widespread acceptance in the Republic of Korea . Given the marketing strategies of the big tobacco companies, the world‐wide market share of nicotine‐containing products accounted for by HTPs is likely to grow, increasing the potential for public health concern.…”
mentioning
confidence: 99%